Oviposition Decisions by Indianmeal Moth - Pierce, Josie; Campbell, James (My University, 2018)
The Indianmeal moth, Plodia interpunctella,is a pest in the United States of stored grains. The larvae feed on grains, grain products, dried fruits, nuts, cereals and a variety of processed food products. Indianmeal moths can detect where other Indianmeal moths have laid eggs but it is unknown if they know where other species have been and laid eggs. So, does the colonization of flour by other species affect where an Indianmeal moth will lay her eggs? Our results showed there was no preference for colonized or uncolonized flour by the moths. The average number of eggs laid in both patches of flour was even. This data shows us that the moths do not have a preference where they lay their eggs, potentially increasing competition among species in food patches.
Keywords: Fall 2018